Pengaruh Kemampuan Kerja, Motivasi Dan Komitmen Organisasi Terhadap Kinerja Pegawai Kantor Camat Manduamas Kabupaten Tapanuli Tengah - Ardi Ansyah Harahap; Vicky Yansen Jefriando; Wenny Wahyuni; Rizky Bagustianto (Manajemen dan Bisnis, 2022)
This formula research internal issue is how influence of  job ability on employees performance.  How influence of motivation  on employees performance. How influence of organization commitment on employees performance. How influence of  job ability, motivation  and  organization commitment  on employees performance. This research target is to for know influence and analyze of job ability on employees performance. For know influence and analyze  motivation  on employees performance. For know influence and analyze organization commitment  on employees performance. For know influence and analyze job ability,   motivation and  organization commitment  on employees performance. Sample in this research amount to 34 employees. Technique analyze data which used in this research is analysis of regresi multiple linear. This research result explain of  job ability effect positive and significant on employees performance.  Motivation  effect positive and significant on employees performance.  Organization commitment  effect positive and significant on employees performance .Job ability, motivation  and  organization commitment  effect and positive and significant on employees performance